TINJAUAN DAYA INOVASI PEMERINTAH DAERAH DALAM PELAKSANAAN DESENTRALISASI DI KABUPATEN/KOTA PROVINSI KALIMANTAN TIMUR - Hutauruk, Thomas R. (Pusjar SKPP Lembaga Administrasi Negara, 2010)
The local government here how can overcome existing problem. To that's local government have to can develop;build harmonious and harmonic relation with corporate world and society to realize to arrange good governance. Essensi from delivering birth of Law No. 32/2004 and Law No. 33/2004, for example are: Variety in unity, Political paradigm, using democracy principle, justice and generalization. Economic paradigm which emphasize at area competitiveness in face of global emulation through enableness of society. Problem of arising out along with journey of Autonomy Area, the local government have conducted stages;steps of inovatif in exploiting of natural sumberdaya and also available human being sumberdaya. When powered existing excellence in an optimal fashion of course will be able to move forward area economics marked with prosperity of society. But, if such excellence just for simply fulfilling formal ground, hence society will not obtain;get something benefit. Pursuant to its source, hence writer divide to become innovation of adoptif, innovate self-supporting innovation and instruktif. Result of research conclude, that 1) Ability of Municipalities innovation in Kaltim still relative lower 2) paradigm of governmental as steward of society not yet fully run; and 3) Condition of politically in labile center storey level cause doubt of leadership in area. Keywords: innovation, local government